The Force Degradation Study of The Morpholinium 2-((4-(2-Methoxyphenyl)-5-(Pyridin-4-YL)-4H-1,2,4-Triazol-3-YL) Thio) Acetate - Varynskyi, Borys; Kaplaushenko, Andriy (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
The aim of the current research was to make force degradation study of the morpholinium 2-((4-(2-methoxyphenyl)-5-(pyridin-4-yl)-4H-1,2,4-triazol-3-yl)thio)acetate (API) for additional confirmation of the selectivity of API and impurity determination method, propose possible structures of degradation products. Agilent 1260 Infinity (degasser, binary pump, autosampler, column thermostat, diode array detector) was used. Mass selective detector was single-quadrupole LC/MS 6120 with electrospray ion source (ESI). The chromatography study was carried out by isocratic elution with a water-acetonitrile mixture (84:16) with the addition of 0.1% methanoic acid. A column Zorbax SB-C18, 30 mm x 4.6 mm, 1.8 um. A column temperature was 40oC. The flow rate was 0.400 ml/min. The period of exposition of stress factors was four days. The period of exposition of stress factors was four days. Influence of the such factors as acid, alkali, H2O2, temperature, UV radiation on the API in bulk drug, 0.1% solution and 1% â€œsolution for injectionâ€ were studied. Dependence of content of API from a number of days of factors exposition was studied. Most destructive action was during the influence of the H2O2 and UV radiation. API was stable during the storage at laboratory conditions, acid, alkali and temperature (60oC) influence. Some degradation products structure was proposed.Â